Surface Complexes of Cr(VI) by Eucalyptus Barks - Hind Khalil; Fatima Ezzahra Maarouf; Mariam Khalil; Sanaa Saoiabi; Saidati Bouhlassa; Ahmed Saoiabi; Mhamed Hmamou; Khalil Azzaoui (Universitas Gadjah Mada, 2022)
The sorption mechanism of hexavalent chromium sorption on eucalyptus barks was evaluated as a function of solution pH for different adsorbent dosages, surface coverage, and the amount of adsorbent. The chromium retention was evaluated based on the distribution coefficient (D), and this retention is attributed to species, which is predominant between pH 1 and 6.5. The biosorption of Cr(VI) ions onto barks achieved at pH 2.0 in the highest sorbet conditions corresponding to [Cr(VI)] = 10–5 mol (V = 100 mL) is examined for various surface coverage. The surface complexes formed between chromate and eucalyptus barks were found to be > S (HCrO4) and > S (CrO4). Logarithmic stability for log K1–1 and the log K10 values of the complexes were measured and found to be -5.93 in acidic medium and -0.76 in alkaline medium, respectively. Pointed out that the adsorption of Cr(VI) on eucalyptus bark was greater than 90% in all cases, Cr(VI) recovery is strongly acidic dependent and shows maximum retention, for various sorbent amounts, at pH around 2, and this retention is attributed to species, which is predominant between pH 1 and 6.5, the morphological surface of eucalyptus barks were examined by Scanning Electron Microscope (SEM) connected to a micro analyzer EDS.